(untitled) (American Journal of Islam and Society, 2015)
This volume of scholarship surrounding Islamic fashion presents a counternarrative to a dominant story: that Muslim women in the West are subjugated by the oppressive and patriarchal yoke of Islam. Islamic Fashion and Anti- Fashion: New Perspectives from Europe and North America offers a fresh new look at veiling, its intersection with religious piety, family, community, religious authority, fashion, and commoditization through sixteen distinct stud- 104 The American Journal of Islamic Social Sciences 32:2 ies ranging from clothing items like the burqini and the pardosu to larger issues surrounding identity and politics, such as North American Islamophobia and its impact on Canadian Muslims. This book represents a large field of research on Muslim women’s lived experiences, one that reveals the complexities inherent in these religious actors whose choices of dress reveal a large set of competing values, desires, and commitments. The book is organized into five sections: location and encounter, history and heritage, the marketplace, fashion and media, and fashion and anti-fashion. Two of its attractive features are the numerous black and white images running through many of the chapters, as well as the two groups of stunning, provocative color photographs showing the richness of Islamic fashion, from “hijabi street style” to London Muslim hipster style ...